Management of river basins from spatial and socio-environmental perspectives - Nascimento Lopes, Elfany Reis do (2020)
The study aimed to methodologically subsidize the socioenvironmental analysis of river basins, based on the use of secondary social economic and environmental data in the Una river basin, Ibiuna, Silo Paulo, Brasil Secondary data were screened, using Pearson's correlation, multiple linear regression, and a spatial socio-environmental quality index. There was a strong correlation between the economic characteristics of households and their occupants with environmental sanitation. The quality index revealed better socio-environmental conditions in the urban area, contributing to the identification of areas requiring intervention that include the rural area, because these am sites with relevant social economic and conservation interests of water resources.